Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus isolates in Eastern China - Jiang, Chunyan; Zhang, Xiaoju; Han, Jianfeng; He, Haijian; Zhang, Chaoying; Zhang, Hongbing; Jin, Jingjing; Wang, Liang; Ge, Bingqian; Wang, Yanli; Liu, Yongjie (The Journal of Infection in Developing Countries, 2018)
Introduction: Porcine epidemic diarrhea virus (PEDV) is one of the most common viral pathogens causing swine diarrhea. Methodology: We performed a genetic evolution analysis of the S1 gene of endemic PEDV strains in Eastern China. The S1 genes of 37 PEDV-positive samples were amplified and sequenced, and compared to the standard CV777 strain, 120 nucleotides were found to have mutations. Results: The nucleotide and deduced amino acid homologies between the sequences and those of the CV777 strain were 90%–91% and 88.2%–90%, respectively, and their homologies to the vaccine strain were 88.6%–89.7% and 86.2%–87.8%, respectively. Genetic evolution and variation analyses indicated that the 37 PEDV strains belonged to genogroup 2-1, while the CV777 strain, vaccine strain, and earlier Chinese strains all belonged to genogroup 1-1. Conclusions: The newly emerged clinical PEDV strains indicate that the PEDV CV777 vaccine currently used in China may not fully protect pigs from infection with recent epidemic strains, and will require the development of new vaccine strains.